"Venturing into the unknown"?: method(olog)ical reflections on religion and digital games, gamers and gaming - Heidbrink, Simone; Knoll, Tobias; Wysocki, Jan (Online - Heidelberg journal of religions on the internet, 2015)
Digital games research has finally been accepted in ‘serious academia’ as the multitude of new scientific publications clearly show. There is an abundance of case studies whereas thorough methodological and methodical groundwork is hardly to be found. A void that is reflected by some (from an academic viewpoint) rather disputable practical approaches. This article is trying to fill that void by offering some methodical considerations, striving for starting up methodical discussions in academia.Derived directly from the ‘digital fieldwork’ in different game spheres and from the perspective of cultural studies, the authors give a practical and basic introduction into methods applicable for researching different aspects and occurrences of religion in digital games, gamers and the practice of digital gaming. The methodical discussion is illustrated by examples derived from a case study on Smite, a multiplayer online battle arena game published by Hi-Rez in 2014 and are preceded by a short summary on theoretical and methodological preconditions and considerations.